357 Risk of unintentional injury in children with sensory impairment. (1st September 2016) - Cherry, Jocelyn; Mytton, Julie; Hall, Amanda; Williams, Cathy
Abstract : Background: Unintentional injury (UI) is a leading cause of death in <15s. Children have less ability to process and synthesise complex sensory information. Children with sensory impairment (SI), whether visual impairment (VI) or hearing impairment (HI), are at increased risk as they have incomplete development summated with SI. Methods: Medline (from 1950), Embase, AMED and PsychINFO were searched to Week 36, 2013. The search string was designed to maximise sensitivity. PICO was P:Children from birth to 18 I: SI defined by the study authors as 'significant' C: Not impaired O: UI – medically attended or self-care. Exclusion criteria were papers with mixed ages with no separate children's data, varied impairments (I) with no outcomes by I, or mixed levels of I with no separate data for significant I. The systematic review was registered with PROSPERO, the International Prospective Register of Systematic Reviews. Results: 16, 466 articles were title reviewed and 15, 290 excluded. 1, 176 abstracts were reviewed and 1, 139 excluded. Grey literature searching identified a further paper. 38 full papers were reviewed with 16 articles included. 22 articles were excluded. A narrative synthesis of the heterogenous data found increased risk of UI with increasing age, male sex, being from an ethnic minority, of low socio-economic status, having low activity levels and for dental UI specifically risk was increased with overjet > 3.5 mm, severe malocclusion, inadequate lip coverage and poor oral health. No cohort studies or trials were found. No research was found covering some of the major types of childhood UI such as drowning or fire-related UI. Nor covering the effect of the severity of the impairment on UI risk. Nor covering effect of comorbidities on UI risk in SI. Conclusions: Little is currently known about the impact of SI on UIs. This review suggests SI increases a child's risk of UI. Surprising gaps in evidence were found. Further high-evidence level studies are needed.